Sinonasal tumours: a clinical study and management - Sawant, Shweta; Megalamani, Somanath B. (International Surgery Journal, 2017)
Background: Sinonasal tumours are rare. Malignant lesions are more common than benign ones and prognosis is grave. This study was undertaken to understand clinical and histological features in addition to diagnostic workup, treatment outcomes, survival and prognostic factors of sinonasal tumours. Methods: Time bound descriptive study at Department of ENT, KIMS, HUBLI, of 31 patients presenting with features suggestive of sinonasal tumours from October 2014 to September 2016. All patients were subjected to diagnostic nasal endoscopy, biopsy and radiological assessment of nose and paranasal Sinuses. Results: 31 patients with sinonasal tumours were included in study group. Male patients outnumbered the female patients (2.4:1). Cigarette smoking was found to be important risk factor and was statistically significant(p<0.05). Patients mainly presented with complaints like nasal obstruction, nasal discharge, headache, hyposmia/ anosmia, facial swelling, facial pain, etc. Malignant tumours were more than benign tumours. JNA and IP were most common among benign and SCC was most common among malignant tumours. Conclusions: Sinonasal tumours are rare. Early diagnosis is important. Nasal endoscopic examination and CT scan can diagnose sinonasal tumours at an early stage. With many etiological factors analysed, cigarette smoking was found to be an important risk factor even for sinonasal tumours.